1981
DOI: 10.1210/endo-108-4-1379
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Induction of Luteinizing Hormone Receptor in Cultured Rat Granulosa Cells: An Examination of the Need for Steroids in the Induction Process*

Abstract: The induction of LH receptors by FSH in cultured rat granulosa cells and the effects of ovarian steroids on this process were examined. Granulosa cells were isolated from the ovaries of untreated immature rats (25 days old) and cultured with highly purified FSH (Sairam; 250 ng/ml). After culture (48-96 h in chemically defined media), both the binding of [125I]hCG and the responsiveness (cAMP and progesterone production) to an acute LH stimulus (100 ng/ml; NIH B8) were measured. The appearance of LH/hCG-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
2

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 22 publications
2
10
0
2
Order By: Relevance
“…Similar to an earlier study suggesting that the continuous presence of FSH is necessary for LH receptor maintenance (10), the present studies indicate that LH is also capable of enhancing LH receptors in FSH-primed granulosa cells in vitro. Time-course studies indicate that the LH receptor content is increased within 12 h of initiation of LH treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to an earlier study suggesting that the continuous presence of FSH is necessary for LH receptor maintenance (10), the present studies indicate that LH is also capable of enhancing LH receptors in FSH-primed granulosa cells in vitro. Time-course studies indicate that the LH receptor content is increased within 12 h of initiation of LH treatment.…”
Section: Discussionsupporting
confidence: 91%
“…2. Consistent with previous observations (9)(10)(11), FSH treatment produced a dose-dependent increase in LH receptor content ( Fig. 2A, ) compared to that of FSH-primed cells without further hormone exposure.…”
Section: Stimulation Of Lh Receptor Content and Progesterone Productisupporting
confidence: 92%
See 1 more Smart Citation
“…A possible role for progesterone as a mediator of FSH induction of LH receptors has been suggested previously (5). Therefore, to examine directly whether progesterone is involved in the induction process of LH receptors by FSH, we studied the effect of aminoglutethimide on FSH-mediated LH receptor induction.…”
Section: Resultsmentioning
confidence: 97%
“…1 for review). In recent years, several different systems have been described in which primary cultures of granulosa cells are maintained such that they retain their ability to respond in vitro to FSH with an increase in the density of LH receptors (2)(3)(4)(5)(6). It has been shown that the ability of FSH to induce LH receptors in granulosa cells is due to its ability to activate adenylate cyclase because other compounds that stimulate adenylate cyclase, such as cholera toxin, or the direct addition of cAMP or its analogues to the cells also cause the appearance of LH receptors (4,(7)(8)(9)).…”
mentioning
confidence: 99%